Pandangan Mahasiswa Semester 4 STKIP Muhammadiyah Manokwari Terhadap Film 172 Days Karya Nadzira Shafa dengan Pendekatan Semiotik - Samara, Nisha; Rahmi, Elvi; Yaqinah, Ainul (LP4MK STKIP PGRI Lubuklinggau, 2025)
This research aims to analyze the views of fourth-semester students on the film 172 Days by Nadzira Shafa using a semiotic approach. This film tells the spiritual journey of Nadzira Shafa, who transforms from a free-spirited life to making a hijrah after meeting Ameer Azzikra. The method used in this research is descriptive qualitative. The research results show that the community views this film as a representation of the hijrah process, which is full of challenges yet meaningful, with an emphasis on the values of sincerity, patience, and responsibility in living a religious life. Additionally, this film is also viewed as an effective medium for preaching, conveying Islamic messages in a contemporary manner. This research is expected to contribute to understanding the role of film media as a communication tool in society and to enrich semiotic studies in the context of culture and religion.